200 Jahre Entwicklung in der kontinuierlichen Destillation. Issue 12 (16th October 2013) - Kockmann, Norbert
<x xml:space="preserve">Abstract</x> Distillation is the oldest and today most frequently used separation and purification method. In 1813, Jean‐Baptiste Cellier‐Blumenthal patented the first continuously working distillation column, starting an impressive development of process equipment. New product areas were discovered as well as improved equipment installations. Current developments are guided by deeper knowledge of heat and mass transfer as well as the integration of various process functions.